Modulation of Immune Responses to Influenza A Virus Vaccines by Natural Killer T Cells - Driver, John P.; de Carvalho Madrid, Darling Melany; Gu, Weihong; Artiaga, Bianca L.; Richt, Jürgen A. (Frontiers in Immunology, 2020)
Influenza A viruses (IAVs) circulate widely among different mammalian and avian hosts and sometimes give rise to zoonotic infections. Vaccination is a mainstay of IAV prevention and control. However, the efficacy of IAV vaccines is often suboptimal because of insufficient cross-protection among different IAV genotypes and subtypes as well as an inability to keep up with the rapid molecular evolution of IAV strains. Much attention is focused on improving IAV vaccine efficiency using adjuvants, which are substances that can modulate and enhance immune responses to co-administered antigens. The current review is focused on a nontraditional approach of adjuvanting IAV vaccines by therapeutically targeting the immunomodulatory functions of a rare population of innate-like T lymphocytes called invariant natural killer T (iNKT) cells. These cells bridge the innate and adaptive immune system and are capable of stimulating a wide array of immune cells that enhance vaccine-mediated immune responses. We discuss the factors that influence the adjuvant effects of iNKT cells for influenza vaccines as well as obstacles that must be overcome before this novel adjuvant approach can be considered for clinical or veterinary use.